The Sustainability of Islamic Education in Rural Communities in Indonesia - Fery Diantoro; Aris Nurbawani (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2025)
This study is based on the dynamics occurring in rural communities, particularly related to limited Islamic religious knowledge and inadequate access to education, which need to be addressed through the development of sustainable Islamic education. The sustainability of Islamic education is key to changing social conditions and empowering rural communities. The purpose of this study is to identify the model of Islamic education at Griya Pintar Mbok Supi, Gading Village, the basis for building its sustainability, and the factors that influence it. The method used is field research with a qualitative and phenomenological approach, which allows for in-depth analysis of the experiences of education practitioners and the surrounding community. This study focuses on how the educational model is implemented, the basis for building educational sustainability, and the factors that influence the sustainability of Islamic education at the institution. Key findings indicate that the model of Islamic education at Griya Pintar Mbok Supi, Gading Village, is a form of community-based Islamic education that takes place in residents' homes through non-formal education channels. Its sustainability is built on the basis of strong da'wah motivation, basic capital in the form of a home as a place of education, social capital built through harmonious relationships with the community, and the utilization of local potential. Factors that influence its sustainability include the open and adaptive attitude of the community, awareness and concern for Islamic education, good communication, and support from the government and stakeholders.